2016
DOI: 10.1515/ijamh-2016-0031
|View full text |Cite
|
Sign up to set email alerts
|

The parental role in adolescent screen related sedentary behavior

Abstract: Perceived parental screen time rules play a role in the amount of screen time among adolescents. Interventions that focus on parental limit setting development and physical activity support may be effective in decreasing screen time among youth aged 13-15 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
4
0
3
Order By: Relevance
“…Apart from a few other research studies examining the relationship between SB and parental rules, this study also investigated this relationship ( Tandon et al, 2012 , Bounova et al, 2016 , Pearson et al, 2011 , Gingold et al, 2014 , Salmon et al, 2005 ). The BEAP Study found that the absence of parental rules regarding screen time was associated with a higher odds of solitary SB-Frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a few other research studies examining the relationship between SB and parental rules, this study also investigated this relationship ( Tandon et al, 2012 , Bounova et al, 2016 , Pearson et al, 2011 , Gingold et al, 2014 , Salmon et al, 2005 ). The BEAP Study found that the absence of parental rules regarding screen time was associated with a higher odds of solitary SB-Frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed findings regarding how the presence, number, or type (younger vs., older) of sibling are associated with children's sedentary behaviour and/or screen-time[121,[136][137][138]. Household practices (n = 84)• Children who lived in a family with screen-time restrictions spent less time engaged in screen-based behaviours[126,133,[139][140][141][142][143][144][145][146][147][148][149].• Electronics in children and youth's bedrooms were associated with increased time spent in screen viewing[110,111,134,[150][151][152][153][154][155][156].• Number of electronics in the household was a positive predictor of screen viewing[144,157].• Eating meals in front of the TV was linked with greater sedentary behaviour and screen viewing[134,144,[157][158][159].…”
mentioning
confidence: 99%
“…The adolescents in the study group should be provided with education and advice concerning the use of smart signs. Previous studies have shown that parents who set rules on media consumption and serve as positive role models can help to reduce the time adolescents spend in front of the screen [27][28][29][30]. Although parental supervision and the frequencyof family TV time decreases as children grow older, families should regulate the purpose and content of children's media use, restrict the amount ofuse, and provideexplanatory assistanceto children by using the media with them.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, participants spent 2.2 hours daily in front of a screen [31]. Another study found that adolescents spent a daily average of 193 minutes in front of ascreen [27]. Haines et al [32] found that 33.7% of females and 43.9% of males spent two hours and more in front of a screen daily.…”
Section: Discussionmentioning
confidence: 99%